2015
DOI: 10.1007/s10384-015-0378-0
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal injection of melphalan for intraocular retinoblastoma

Abstract: The risk of extraocular tumor spreading following intravitreal injections is low, and other adverse events are rare. Sixty-eight percent of the treated eyes achieved complete vitreous seed remission, and about half of them retained practical levels of vision. The intravitreal injection of melphalan is a safe and effective treatment for vitreous seeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 22 publications
0
44
1
1
Order By: Relevance
“…Intravitreal delivery of chemotherapy is not without its own set of side effects, including retinal toxicity as described by Munier [14]. Suzuki et al [22] reported findings for anterior toxicity, including iris atrophy and dense cataracts, in 8.7% of eyes (23/264) and diffuse chorioretinal atrophy in 0.8% of eyes (2/264). Ghassemi and Shields [23] reported RPE changes, cataracts, and phthisis in 25% of eyes (3/12).…”
Section: Discussionmentioning
confidence: 95%
“…Intravitreal delivery of chemotherapy is not without its own set of side effects, including retinal toxicity as described by Munier [14]. Suzuki et al [22] reported findings for anterior toxicity, including iris atrophy and dense cataracts, in 8.7% of eyes (23/264) and diffuse chorioretinal atrophy in 0.8% of eyes (2/264). Ghassemi and Shields [23] reported RPE changes, cataracts, and phthisis in 25% of eyes (3/12).…”
Section: Discussionmentioning
confidence: 95%
“…Recently, Suzuki et al [8] described their 21-year experience with intravitreal melphalan injections for vitreous seeding in retinoblastoma. They reported on 2 cases of diffuse chorioretinal atrophy associated with intravitreal melphalan injections.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, while scleral thinning following bevacizumab has been visualized with OCT 9 , it seldom involves a rarity of scleral tissue with visualization of the underlying uvea as was seen in our case. It is possible that the melphalan contributed to atrophy/necrosis of the ocular surface, in a similar manner that has been found with the iris, choroid, RPE and retina 1,4,14,15 . On the other hand, the scleral pigmentation may simply represent migrated deposition of released pigments from nearby retina, ciliary body or iris.…”
Section: Discussionmentioning
confidence: 55%